Evaluation of CSR Implementation and Improvement Strategy Using SWOT Analysis and Balanced Scorecard Perspective (Case Study on Upstream Oil and Gas Production Operations in Pertamina EP Jatibarang Field) - Duddy Muzahid; Wahyuningsih Wahyuningsih (Journal of Social Research, 2023)
This study aims to evaluate the implementation and provide an overview of strategies to improve social responsibility programs using the balanced scorecard method and SWOT analysis as part of the company's role in sustainable development and social empowerment. This research approach is qualitative. The research location is at PT Pertamina EP Jatibarang Field. Time of research in 2023. Primary data collection techniques through in-depth interviews and secondary data based on company internal data. The data analysis technique uses the balanced scorecard which is a performance management system that combines 4 main measurement categories, namely the public perspective, internal business perspective, financial perspective, and learning & growth perspective, and SWOT analysis. The results of the research show that PT Pertamina EP Jatibarang Field has carried out CSR activities for a long period of time, so it can take advantage of various long experiences in CSR to increase the effectiveness of subsequent CSR programs, then continue practical training programs that are useful for direct implementation by the community/community as a basis for empowerment. Pertamina EP needs to revamp the CSR budget management so that the allocation and supervision are more effective, and it needs to develop the partnerships that have been formed (Elpiji Gas Project for the Environment, Organic Agriculture).